Nuclear astrophysics : a course of lectures - Khan, Md A. (Boca Raton, Fla. : CRC Press, 2018)
"In this volume the physics involved in various astrophysical processes like the synthesis of light and heavier elements, explosive burning processes, core collapse supernova etc have been critically addressed with minimum mathematical derivations so as to suit all faculties of the readers. For graduate students there are solved problems with exercises at the end of each chapter, for researchers some recent works on the calculation of physical parameters of astrophysical importance like the calculation of Sfactors at low energies have been included, and for amateur readers there are lot of history, information and discussion on the astronuclear phenomenon.Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka."--Provided by publisher.
chapter 1 Basics of Nuclear Astrophysics / Md A Khan -- chapter 2 Nucleosynthesis / Md A Khan -- chapter 3 Sources of Energy in Stars / Md A Khan -- chapter 4 Opportunities in Nuclear Astrophysics / Md A Khan -- chapter 5 Explosive Burning Processes / Md A Khan -- chapter 6 Core Collapse Supernovae / Md A Khan -- r
Keywords: Nuclear astrophysics; Particles (Nuclear physics)